Influence of fixed orthodontic appliances on the change in oral Candida strains among adolescents - Yan Zheng; Zhenya Li; Xiangyi He (Journal of Dental Sciences, 2016)
Background/purpose: The aim of this study was to explore the presence and variability of oral Candida in adolescents before and during treatment with fixed orthodontic appliances. Materials and methods: A total of 50 patients aged 10–18 years old were randomly selected for this study. Microorganism samples were obtained prior to and after orthodontic treatment and identified by culture methods. Molecular biology techniques were used to investigate the samples further and the effect of the orthodontic appliance on oral pathogenic yeasts was studied longitudinally. Results: The percentage of patients with candidiasis and the total number of colony-forming units significantly increased 2 months after orthodontic treatment. Changes in the type of oral candidiasis prior to and after treatment were significant. Conclusion: Fixed orthodontic appliances can influence the growth of oral pathogenic yeasts among adolescents.